Sulfated peptides: key players in plant development, growth, and stress responses - Zhang, Penghong; Zhao, Jiangzhe; Zhang, Wei; Guo, Yongfeng; Zhang, Kewei (Frontiers in Plant Science, 2024)
Peptide hormones regulate plant development, growth, and stress responses. Sulfated peptides represent a class of proteins that undergo posttranslational modification by tyrosylprotein sulfotransferase (TPST), followed by specific enzymatic cleavage to generate mature peptides. This process contributes to the formation of various bioactive peptides, including PSKs (PHYTOSULFOKINEs), PSYs (PLANT PEPTIDE CONTAINING SULFATED TYROSINE), CIFs (CASPARIAN STRIP INTEGRITY FACTOR), and RGFs (ROOT MERISTEM GROWTH FACTOR). In the past three decades, significant progress has been made in understanding the molecular mechanisms of sulfated peptides that regulate plant development, growth, and stress responses. In this review, we explore the sequence properties of precursors, posttranslational modifications, peptide receptors, and signal transduction pathways of the sulfated peptides, analyzing their functions in plants. The cross-talk between PSK/RGF peptides and other phytohormones, such as brassinosteroids, auxin, salicylic acid, abscisic acid, gibberellins, ethylene, and jasmonic acid, is also described. The significance of sulfated peptides in crops and their potential application for enhancing crop productivity are discussed, along with future research directions in the study of sulfated peptides.